2021
DOI: 10.1038/s41598-021-82019-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of non-thermal plasma jet energy carriers for effective catalytic processing of industrial wastewaters

Abstract: An argon plasma jet was sustained in open air and characterized for its chemical composition. The optically characterized plasma jet was used to treat industrial wastewater containing mixed textile dyes and heavy metals. Since plasma jet produces UV-radiations, the photocatalytic TiO2 was used to enhance plasma treatment efficiency especially for degradation of dyes. Mixed anatase and rutile phases of TiO2 (5.2–8.5 nm) were produced through surfactant assisted sol–gel approach. The emission spectrum confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…The efficiency of chemical processes, involved in DBD discharge, is determined by their cross sections for electron collisions and the decreased field. The emission spectrum of DBD revealed the formation of OH − , N 2 , O, O 3 , NO, N + 2 , O + 2 and O + radicals (Naz et al 2021). A peak at 452 was also detected for CO due to splitting of CO 2 into oxygen and CO.…”
Section: Dbd Plasma Chemistrymentioning
confidence: 97%
“…The efficiency of chemical processes, involved in DBD discharge, is determined by their cross sections for electron collisions and the decreased field. The emission spectrum of DBD revealed the formation of OH − , N 2 , O, O 3 , NO, N + 2 , O + 2 and O + radicals (Naz et al 2021). A peak at 452 was also detected for CO due to splitting of CO 2 into oxygen and CO.…”
Section: Dbd Plasma Chemistrymentioning
confidence: 97%
“…It was observed that the pH of the solution had a significant impact on the photocatalytic degradation of pollutants. To check the role of pH in dye degradation, tests were conducted with different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11) in 1.0 g/L of Ag/TiO 2 and a 3 mM H 2 O 2 oxidant dose. The dye concentrations were 5 ppm, 10 ppm, and 15 ppm.…”
Section: Effect Of Ph On Dye Degradationmentioning
confidence: 99%
“…Among these, nanosized TiO 2 is the most frequently used photocatalyst due to its non-toxic nature, low-cost, high surface adsorption affinity, and distinctive chemical, physical, and optical properties. However, these benefits are only manifested when TiO 2 is applied under the ultraviolet region of the light spectrum, especially for photocatalytic dye degradation applications [5]. TiO 2 is only active under UV radiation due to its high band gap (3.2-3.3 eV), which accounts for just 5% of the solar spectrum, while visible light accounts for 45% of solar spectrum [6].…”
Section: Introductionmentioning
confidence: 99%
“…Here we propose the use of atmospheric plasma as an environmentally sustainable, low energy consumption, affordable and highly efficient method to produce size-controlled and safe noble nanoparticles, which did not absorb toxic chemicals on their surface during the synthesis reaction [15][16][17][18][19]. Cold plasma obtained at atmospheric pressure and room temperature results as being rich with energetic electrons that are capable of dissociating, exciting and ionizing gas molecules [20][21][22]. Typical reactions include the formation of a…”
Section: Introductionmentioning
confidence: 99%